Effect of Fragmented DNA From Plant Pathogens on the Protection Against Wilt and Root Rot of Capsicum annuum L. Plants - Serrano-Jamaica, Luz Maria; Villordo-Pineda, Emiliano; González-Chavira, Mario Martín; Guevara-González, Ramón Gerardo; Medina-Ramos, Gabriela (Frontiers in Plant Science, 2021)
Chili production is affected by wilt and root rot, the most devastating disease caused by the fungal complex of oomycete Phytophthora capsici L. and the fungi Fusarium oxysporum and Rhizoctonia solani, infecting both roots, stems, leaves and fruits. Fungicides are currently inefficient against this disease and have a high environmental impact. DNA fragments of an organism's own origin (conspecific) have shown the ability to inhibit growth and activate defense mechanisms in some plant species. In this investigation, the effect of the fragmented DNA mixture of Phytophthora capsici L., Fusarium oxysporum and Rhizoctonia solani on the protection against wilt and root rot of Capsicum an annuum L. plant was evaluated. Changes in plant performance, phenolics and flavonoids contents, defense-related gene expression and changes in global DNA methylation levels were evaluated. Results showed no significant differences in root density; however, there was a significant decrease in the height of the plants treated with the mixture of DNA fragments. There were significant changes in the content of phenolic compounds and total flavonoids, both associated with defense responses in plants with respect to the control for treatment with fragmented DNA 100 µg mL-1. The highest expression of the phenylalanine ammonium lyase (pal) gene was observed in plants to which the DNA concentration of 100 µg mL-1 was applied, while in the case of superoxide dismutase (Mn-sod) a decrease was observed with respect to control. The percentage of methylation of 5-methyl-cytosine, in plants treated with DNA fragments at a concentration of 100 µg mL-1 and plants treated with DNA fragments at a concentration of 100 µg mL-1 and inoculated with the fungal complex , was significantly increased with respect to the control plants. Finally, by foliar application of the DNA fragments of the fungal complex to a concentration of 100 µg mL-1, a 40% decrease in the mortality of infected plants was achieved compared to the treatment of control plants inoculated with the PCF fungal complex, which indicating a perspective for its application at the agricultural level.